(untitled) (Shanghai, 1989)
Land-use change is ubiquitous. This volume, in bringging together a range of studies presented at a symposium held in Hokaido, Japn, in August 1987,..
Keywords: Land use,Regional planning,Đất; Planning,Hoạch định